Accelerated algorithm in attribute-based encryption over cloud environment - Guowei WU; Ning FAN; Laifu WANG; Shuai WANG; Jun SHEN; Huamin JIN (Dianxin kexue)
Cloud computing provides storage,computing and network services to tenants.Data security and data sharing and access control between tenants are indispensable functions.Attribute-based encryption (ABE) system is a one to many encryption system,which allows users to fine -grained access control on encrypted data according to users’ attributes.This encryption system is very suitable for multi-tenant data sharing overcloud computing environment.However,the existing attribute-based encryption schemes is inefficient,which cannot be applied to practical applications.Two types of ABE and their application scenarios were analyzed,and an acceleration algorithms scheme in attribute encryption cryptosystem was proposed.The experiment can illustrate that the proposed scheme can improve the efficiency of key generation algorithm,encryption algorithm and decryption algorithm.